1999
DOI: 10.3168/jds.s0022-0302(99)75333-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Possible Mechanisms Involved in the Mucosal Immune System Activation by Lactic Acid Bacteria

Abstract: The induction of a mucosal immune response is not easy due to the development of oral tolerance, but under some conditions, bacteria can activate this immune system. Antigens administered orally can interact with M cells of Peyer's patches or bind to the epithelial cells. We have demonstrated that certain lactic acid bacteria are able to induce specific secretory immunity, and others will enhance the gut inflammatory immune response. The aim of this work was to establish the reason for these different behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
8

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 19 publications
6
127
0
8
Order By: Relevance
“…Some studies have shown a reduction in potentially pathogenic organisms even at sites distant to the gut (vagina and nasal cavity) following oral probiotic therapy (Gluck and Olaf Gebbers, 2003;Reid et al, 2003). One proposed mechanism is that probiotics initiate an immune response in the gut-associated lymphoid tissue, resulting in circulation of primed T and B cells and immune activation at distant mucosal surfaces (Perdigon et al, 1999;.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a reduction in potentially pathogenic organisms even at sites distant to the gut (vagina and nasal cavity) following oral probiotic therapy (Gluck and Olaf Gebbers, 2003;Reid et al, 2003). One proposed mechanism is that probiotics initiate an immune response in the gut-associated lymphoid tissue, resulting in circulation of primed T and B cells and immune activation at distant mucosal surfaces (Perdigon et al, 1999;.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration to mice of milk containing L. bulgaricus or L. casei has been shown to activate the lymphocytes and macrophages (Perdigon et al, 1999). Addition of yoghurt to cultures of human blood lymphocytes stimulated by a mutagen leads to increased production of gamma-interferon, a cytokine with anti-proliferative properties that is able to activate natural killer (NK) cells (De Simone et al, 1987).…”
Section: Lactic Acid Bacteriamentioning
confidence: 99%
“…and Lactobacillus spp. were used to prevent some intestinal pathogenic infections and to stimulate the host's immune system in both humans and animals (Perdigón et al 1999, Fang et al 2000, Nakazato et al 2011. It is well documented that Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%